1980
DOI: 10.1111/j.1471-0528.1980.tb04558.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Plasma and Urinary Hormone Levels During and After a Successful Abdominal Pregnancy

Abstract: Summary In a successful abdominal pregnancy, urinary oestriol levels were about the fifth centile, but other hormone concentrations suggested that placental function was normal until 32 weeks gestation. After that, plasma oestrogen concentrations levelled off and plasma placental lactogen concentrations declined. Pre‐eclampsia developed at 34 weeks and necessitated the delivery at 36 weeks and 2 days of a live normal female infant by laparotomy. The placenta was not removed. All hormone levels fell rapidly dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
4
1
1
Order By: Relevance
“…The decrease in serum β‐hCG levels was significantly correlated with the decrease in placental volume ( r 2 = 0.525, P < 0.05). France and Jackson found that placental production of progesterone and estradiol could continue up to 7 weeks postpartum in abdominal pregnancies 14 . The levels of these hormones were not measured in the present study.…”
Section: Commentcontrasting
confidence: 62%
“…The decrease in serum β‐hCG levels was significantly correlated with the decrease in placental volume ( r 2 = 0.525, P < 0.05). France and Jackson found that placental production of progesterone and estradiol could continue up to 7 weeks postpartum in abdominal pregnancies 14 . The levels of these hormones were not measured in the present study.…”
Section: Commentcontrasting
confidence: 62%
“…There was a rapid and sustained improvement in the patient's general condition. Blood samples were collected at regular intervals during the pregnancy and puerperium for hormone analyses which are the subject of a further report (France and Jackson, 1980).…”
Section: Case Reportmentioning
confidence: 99%
“…It has been estimated that the placenta can remain functional for approximately 50 days from the operation, and total regression of placental function is usually complete within 4 months. 17 Complications may include ileus, peritonitis, abscess formation, prolonged hospital stay, and fever. The use of prophylactic methrotrexate is a matter of debate with some favoring its use for subsequent placental shrinkage while others not who advocate that rapid and major degradation of the abdominal placental tissue can result in the accumulation of necrotic tissue, which is an ideal medium for bacterial growth and sepsis.…”
Section: Discussionmentioning
confidence: 99%